Improving intellectual capital model using analytic network process - Wudhikarn R. (2014)
This study proposes a new approach to prioritize the key company's indicators and relative elements following process model of intellectual capital (IC). The IC is improved by the application of analytic network process (ANP). The ANP provides the weights and priorities to all focused key performance indicators (KPIs) serving to the business concept. These obtained weights can also be passed to other relative elements, those of key success factors (KSFs) and IC categories, in the process model of IC. These prioritized KPIs, KSFs and IC categories assist the managers and decision-makers to focus on the crucial elements that mostly affect the business concept.